The Influence Of Communication And The Physical Work Environment On Work Discipline Of Civil Servants At The Tasikmalaya City Education Authorities - Setiawan, Cecep Aris; Karmila, Mila; Patimah, Titin (Journal of Management, Economic, and Accounting, 2024)
The purpose of this study is to find out and analyze the influence of communication and the physical work environment on work discipline of employees who have the statue of civil servants in the Tasikmalaya City Education Authorities. The research menthod used is a quantitative menthod, data obtained directly through questionnaires to 72 respondents who are civil servants at the Tasikmalaya City Education Authorities. Sampling using saturated samples and the analysis method used in this study is multiple linear regression analysis. Based on the result of the study, it shows that the communication and the physical work environment have a positive and significant effect on work discipline of employees who have the statue of civil servants in the Tasikmalaya City Education Authorities. Based on the result of the analysis it is known that the communication and the physical work environment applied simultaneously have a significant effect on work discipline and the communication applied partially have a significant effect on work discipline and the physical work environment applied partyally haven’t significant effect on work discipline of employees who have the statue of civil servants in the Tasikmalaya City Education Authorities.